2021
DOI: 10.3389/fgene.2021.681867
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Autophagy-Related Long Non-coding RNA (ARlncRNA) Signature in Acute Myeloid Leukemia (AML)

Abstract: BackgroundSome studies have proven that autophagy and lncRNA play important roles in AML. Several autophagy related lncRNA signatures have been shown to affect the survival of patients in some other cancers. However, the role of autophagy related lncRNA in AML has not been explored yet. Hence, this study aims to find an autophagy related lncRNA signature that can affect survival for AML patients.MethodA Pearson correlation analysis, a Kaplan–Meier survival curve, a univariate cox regression, and a multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…AML patients can be divided into high-and low-risk groups according to risk score, and we found that the survival was significantly different between the two risk groups. In ROC analysis, the AUC values of 1and 3-year survival were greater than 0.8 in the patients with AML from the TCGA cohort, indicating a superior predictive power in comparison with Zhao et al (2021) (3-year AUC 0.706) and Jiang et al (2021) (3-year AUC 0.711). Notably, risk score was identified as the independent prognostic factor after univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…AML patients can be divided into high-and low-risk groups according to risk score, and we found that the survival was significantly different between the two risk groups. In ROC analysis, the AUC values of 1and 3-year survival were greater than 0.8 in the patients with AML from the TCGA cohort, indicating a superior predictive power in comparison with Zhao et al (2021) (3-year AUC 0.706) and Jiang et al (2021) (3-year AUC 0.711). Notably, risk score was identified as the independent prognostic factor after univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 93%
“…Current studies identify a ferroptosis-or autophagy-related long noncoding RNA signature for predicting prognosis in the patients with AML (Li R. et al, 2021;Zhao et al, 2021;Zheng et al, 2021). Immune-or immune checkpoint-related gene signatures were also developed and validated in AML patients (Li R. et al, 2021;Jiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Among the lncRNAs in the prognostic signature, USP30-AS1 has been reported to be related to autophagy and immunity in bladder cancer ( Wan et al, 2021 ), cervical cancer ( Chen et al, 2020 ) and melanoma ( Ding et al, 2021 ). MIR133A1HG was also reported to be one of the lncRNAs in the autophagy-related signature for AML ( Zhao et al, 2021 ). However, the underlying molecular biological mechanism has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of DNAJB9 in regulating autophagy to influence chemotherapy resistance is unknown, the SNHG5/miR-32/DNAJB9 axis could be an efficient target for developing modalities to increase chemosensitivity in AML patients. Also, a recent study found that a signature containing four autophagy-related lncRNAs (MIR133A1HG, AL359715.1, MIRLET7BHG, and AL356752.1) has the potential as a biomarker to predict the survival of patients with AML [ 158 ]. Moreover, a preprint version of a study suggested that an autophagy-related lncRNA signature containing six lncRNAs (HYMAI, MIR155HG, MGC12916, DIRC3, C1orf220, and HCP5) has important prognostic value [ 159 ].…”
Section: Introductionmentioning
confidence: 99%